2018
DOI: 10.1021/acs.cgd.8b00447
|View full text |Cite
|
Sign up to set email alerts
|

Beadwork and Network: Strings of Silver Ions Stitch Large-π Pyrazolate Patches into a Two-dimensional Sheet

Abstract: Breaking the cycle of silver pyrazolates: instead of the common loops (e.g., the Ag3N6 ring), we report an infinite array in which the equispaced Ag­(I) ions form a zigzag chain, with the associated anthracene bis­(pyrazolate) linkers cofacially aligned one to another. In addition to the strong Ag­(I)–N bonds and the distinct argentophilic interactions, the Ag­(I) ions also form interlayer, metal−π contacts with the anthracene cores. The resultant two-dimensional network exhibits significant electronic interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…Ag–Ag bonds are in the range of 2.389(7)–3.315 (2) Å (av. Ag–Ag = 2.953 Å) which is comparable with the earlier literature. There are four sulfate units with average S–O bond distances of 1.443 Å. The sulfate unit possesses an average angle of 109.4°, which is indicative of a regular tetrahedral arrangement.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Ag–Ag bonds are in the range of 2.389(7)–3.315 (2) Å (av. Ag–Ag = 2.953 Å) which is comparable with the earlier literature. There are four sulfate units with average S–O bond distances of 1.443 Å. The sulfate unit possesses an average angle of 109.4°, which is indicative of a regular tetrahedral arrangement.…”
supporting
confidence: 85%
“…Such Ag•••Ag interactions are more significant for silver-based framework materials. 42,43 Beside the silver sulfate compounds, Jin et. al have also communicated one octanuclear Ag 8 -cluster stabilized with adamentanedicarboxylic acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the twisted structure prevents the formation of a trap for the charge carriers and facilitates the conductivity. 53,54 In the present study, the shortest π⋯π contact was observed in 2 as 3.219 Å compared to 3.315 Å in 1, indicating that the former should show better conductivity. However, the zig-zag type hydrogen-bonded layered structure in 1 compared to the almost planer H-bonded sheet structure in 2 may reduce the trapping time of the charge carriers, making 1 a better semiconducting material.…”
Section: Crystengcomm Papersupporting
confidence: 46%
“…The shorter the separation in the molecular stacking, the higher the conductivity of the materials. Additionally, the twisted structure helps to prevent the formation of charge carrier traps and hence enhances conductivity by reducing holding time. , In the present case, polymorph I exhibits the shortest π···π contact of 3.322 Å, whereas polymorph II has a slightly longer separation of 3.491 Å, suggesting that polymorph I may display better conductivity. However, the tilted molecular plane in polymorph II , compared to the nearly planar molecule in polymorph I , reduces the trapping time of the charge carriers, thereby making polymorph II a superior semiconducting material.…”
Section: Resultsmentioning
confidence: 60%